2003
DOI: 10.1073/pnas.1836391100
|View full text |Cite
|
Sign up to set email alerts
|

Drosophila spalt/spalt-related mutants exhibit Townes-Brocks' syndrome phenotypes

Abstract: Mutations in SALL1, the human homolog of the Drosophila spalt gene, result in Townes-Brocks' syndrome, which is characterized by hand͞foot, anogenital, renal, and ear anomalies, including sensorineural deafness. spalt genes encode zinc finger transcription factors that are found in animals as diverse as worms, insects, and vertebrates. Here, we examine the effect of losing both of the spalt genes, spalt and spalt-related, in the fruit fly Drosophila melanogaster, and report defects similar to those in humans w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
0
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 58 publications
2
41
0
1
Order By: Relevance
“…Five loci were previously shown to be expressed sexdifferentially in L3 genital discs. Of these, all five were significantly differentially expressed in our analysis at a stringent FDR threshold of 0.05: bnl and btl ; abdominal A (abd-A) (Freeland and Kuhn, 1996;Casares et al, 1997;Chen et al, 2005); Wnt oncogene analog 2 (Wnt2) (Kozopas et al, 1998); and the paralogous, adjacent spalt (sal) genes (Dong et al, 2003). Additional significant loci can be considered positive controls as well, although their expression in genital discs had not been quantified directly: the female-specific dsx isoform; malespecific lethal 2 (msl-2), which shows lower mRNA levels in whole females than males (Bashaw and Baker, 1997); bab1/2, the protein expression of which in L3 discs appears different in males and females but had not been quantified (Couderc et al, 2002); Pox neuro (Poxn), which was shown to be expressed in male discs at time points later than ours (Boll and Noll, 2002); and stumps, which appears upregulated in btl-expressing cells as they transition to epithelium and which shows, consistent with this observation, significantly male-biased expression at P6 and P20 but not L3.…”
Section: Resultsmentioning
confidence: 87%
“…Five loci were previously shown to be expressed sexdifferentially in L3 genital discs. Of these, all five were significantly differentially expressed in our analysis at a stringent FDR threshold of 0.05: bnl and btl ; abdominal A (abd-A) (Freeland and Kuhn, 1996;Casares et al, 1997;Chen et al, 2005); Wnt oncogene analog 2 (Wnt2) (Kozopas et al, 1998); and the paralogous, adjacent spalt (sal) genes (Dong et al, 2003). Additional significant loci can be considered positive controls as well, although their expression in genital discs had not been quantified directly: the female-specific dsx isoform; malespecific lethal 2 (msl-2), which shows lower mRNA levels in whole females than males (Bashaw and Baker, 1997); bab1/2, the protein expression of which in L3 discs appears different in males and females but had not been quantified (Couderc et al, 2002); Pox neuro (Poxn), which was shown to be expressed in male discs at time points later than ours (Boll and Noll, 2002); and stumps, which appears upregulated in btl-expressing cells as they transition to epithelium and which shows, consistent with this observation, significantly male-biased expression at P6 and P20 but not L3.…”
Section: Resultsmentioning
confidence: 87%
“…The stalk and socket walls are stiffened so that all movement is translated into a rocking of the ring-joint on its vertical axis [37]. Formation of this specialized organ from epidermal cells requires the redundant zinc-finger proteins encoded by spalt (sal) and spaltrelated (salr): sal salr double mutants have fused segments and disorganized scolopidia and are completely deaf [23].…”
Section: Chordotonal Organ Structure and Functionmentioning
confidence: 99%
“…[15][16][17][18][19] Human SALL4 mutations are associated with Duane radial ray syndrome (or Okihiro syndrome). 3,[20][21][22] Duane radial ray syndrome is a human autosomal-dominant syndrome involving radialsided hand anomalies in association with Duane syndrome.…”
mentioning
confidence: 99%